IoT-Based Machida Cultivation Method Implementation in Hydroponic System to Increase Melon Crop Productivity - Knight, Guntur Petrus Boy; Manalu, Istas Pratomo; Silalahi, Sari Muthia (Journal of Electrical, Electronics and Informatics; Vol 7 No 1 (2023): JEEI (July 2023), 2023)
National consumption of fruits in Indonesia is expected to increase. The reasons for this are the awareness of Indonesian about the health effect of fruits consumption and the demographic bonus that will increase Indonesian economic output which in turn increase the consumption of fruits in the long run. Without the increase in fruits production, the price of fruits will increase as a consequence of supply and demand imbalance. In this research we tried to increase the productivity of Melon crops as a study case. Traditional cultivation of melon usually produces 1-2 melons per crop. The purpose of this research is to increase the productivity of Melon crops to at least 8 melons per crop using method such as IoT, Hydroponic system, and Greenhouse. Despite several drawbacks from the initial research design, the result of the research successfully increased the productivity of melon crop as stated in the research purpose.